Pengaruh Model Pembelajaran Guided Inquiry Terhadap Peningkatan Pemahaman Konsep Fisika Siswa Kelas VIII - Delia Sapitri; Nova Kafrita Kafrita; Susy Pransiska (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
Effective learning in physics requires not only memorization but also deep conceptual understanding. Guided inquiry is an active learning approach that encourages students to explore, question, and construct knowledge through structured investigations. This study aimed to investigate the effect of the guided inquiry learning model on eighth-grade students’ conceptual understanding of physics, specifically on vibrations and waves. A quasi-experimental design with a pretest-posttest control group was employed at SMPN 5 Merangin. The study involved 50 students, with 25 in the experimental group and 25 in the control group. Data were collected using a fifteen-item descriptive test designed to measure conceptual understanding. The collected data were analyzed using SPSS Statistics 20, including normality and homogeneity tests, independent and paired t-tests, N-Gain scores, and effect size calculations. The experimental group achieved an N-Gain of 0.66, compared to 0.51 in the control group. Independent t-test results indicated a statistically significant difference between groups (p < 0.05). The effect size was 1.88, suggesting a strong and substantial impact of guided inquiry on students’ understanding. The guided inquiry learning model significantly enhances students’ conceptual comprehension of vibrations and waves, highlighting its effectiveness as an active, student-centered pedagogical strategy in physics education and its potential to improve learning outcomes.